Selection and characterization of broad‐spectrum antibacterial substance‐producing Lactobacillus curvatus PA40 as a potential probiotic for feed additives. (27th August 2018) - Hong, Sung Wook; Kim, Jong‐Hui; Bae, Hyo Ju; Ham, Jun‐Sang; Yoo, Jae Gyu; Chung, Kun Sub; Oh, Mi‐Hwa
Abstract: Lactic acid bacteria were screened for potential probiotics for use as feed additives. We obtained 3, 000 isolates from feces of: cattle, dogs, goats, and infants; milk; yogurt; cheese; fermented sausages; Kimchi ; and Cheonggukjang and tested their antibacterial activity toward indicator pathogens, including Bacillus cereus, Listeria monocytogenes, Escherichia coli O157:H7, and Salmonella enterica Enteritidis. We further tested their tolerance to artificial gastric juice (1% [w/v] pepsin, pH 2.5) and bile acid (0.1% [w/v] oxgall, pH 6.8). Six isolates exhibited strong antibacterial activity against indicator pathogens. The PA40 isolate from Kimchi exhibited marked resistance to artificial gastric juice and bile acid. The antibacterial substances produced by PA40 were stable to heat, pH, and enzymes. Strain PA40 was identified as a Lactobacillus curvatus strain using chemical tests and 16S rDNA sequencing and produced 248.4 mmol/L lactic acid after 48 hr of fermentative growth. The L. curvatus PA40 strain was also highly tolerant of the artificial gastrointestinal model system. Our results indicate that L. curvatus PA40 could be used as a potential probiotic feed additive.